Եվրասիականության և աշխարհագրական դետերմինիզմի նկատմամբ թուրքական զինվորական շրջանակների մոտեցումների շուրջ - Հովսեփյան, Լևոն («Զանգակ - 97»)
In recent years there are also revealed alternative approaches on foreign policy, regional security and defence policy in Turkish military circles. In 1990s the discussions about the Eurasia concept are practised on a large scale in the Turkish political and scientific and also military circles. For some of the Turkish supreme officers Eurasia is considered to be an important geopolitical advantage and possibility. During the Post-cold war period the military-political notions of the Turkish security to a considerable extent carried the influence of “geographical determinism”, by which the particular interests and security of the country are conditioned.
Keywords: Պատմություն; Քաղաքականություն